Student's MC notification system / Noor'ain Mohamed Yunus … [et al.] - Mohamed Yunus, Noor'ain; Abdul Kadir Jailani, Sri Fatiany; Ab Latiff, Dilla Syadia; Said, Noor Azzah; Mat Ali, Syukrina Alini (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
The Student's MC Notification System serves as a platform for faculty to administer students' medical chits (MC). Currently it is found that students 'fake their MC by altering some information on it. Students often give reasons that they have lost their MC thus unable to provide evidence of their absence. Another problem is students have to photocopy their MC and give to their lectures and this would incur the cost and time of the students. The objectives of this system are to ensure that students' MC will be directly channelled to the respective parties and to eliminate MC fraudulent among students. This system offers the greatest advantages to lecturer as it ensures students' MC will be directly sent to the right parties and to eliminate MC fraudulent among students. Another advantage is that the system will effectively manage MC record management. The impact of this system is to enforce discipline culture among students that will create a new environment. It will ensure transparency among lecturers in terms of students' attendance management. It is applicable to adoption in other universities and higher learning institutions setting throughout Malaysia. There is a high potential for commercialization of this system.¬